2022
DOI: 10.1007/s12273-022-0940-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of enhanced green infrastructures for mitigating urban heat in a desert urban setting

Abstract: The cities of desert climates are anticipated to recognize a synergy of urban heat island (UHI) and severe heat waves during summertime. To improve the urban thermal environment, the present study aims quantitatively explore a strategically designed network of vegetation patches called green infrastructure (GI) in subtropical desert cities such as Dubai. To achieve a more comfortable temperature environment, we built and simulated four GI situations with higher GI fractions, GI25, GI50, GI75, and GI100. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…16). By lowering the urban surface temperature, the height of the planetary boundary layer may decrease, resulting in reduced heat advection from the desert 24 .…”
Section: Resultsmentioning
confidence: 99%
“…16). By lowering the urban surface temperature, the height of the planetary boundary layer may decrease, resulting in reduced heat advection from the desert 24 .…”
Section: Resultsmentioning
confidence: 99%
“…It is a crucial metric for assessing the quality of urban life and the capacity for sustainable development. Researchers delineate vitality through diverse factors such as heatmap data [44], mobile signaling data [44], nighttime light data [45], and online check-in data [42,46].…”
Section: Space Vitalitymentioning
confidence: 99%
“…The warmer climate, expanding urban boundaries and increasing population have created unprecedented hot weather in cities (Santamouris 2023a(Santamouris , 2023b. Urban overheating is imposing detrimental effects on energy consumption (Santamouris 2014b;Khan et al 2023a;Mohammed et al 2023a), and peak electricity demand (Sigauke and Nemukula 2020). Studies on major US cities have shown that a 1 °C increase in temperature, once it exceeds 15-20 °C, results in a 2%-4% increase in peak electricity demand (Cao et al 2010).…”
Section: Introductionmentioning
confidence: 99%